2019
DOI: 10.1039/c8ra09049a
|View full text |Cite
|
Sign up to set email alerts
|

Improved control on the morphology and LSPR properties of plasmonic Pt NPs through enhanced solid state dewetting by using a sacrificial indium layer

Abstract: Fabrication of Pt NPs with the improved configuration, spacing, uniformity and localized surface plasmon resonance (LSPR) response is demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…This shape evolution was also observed in solid-state dewetting of 40 nm Pt films on an adhesion layer of ZnO where faceted Pt islands changed to rounded shape with longer annealing time at 900 °C. 30 Kunwar et al 31 observed the change in the Pt NP shape from irregular to semispherical to hexagonal when the temperature was increased from 700 to 900 °C in their work on using an In sacrificial layer to enhance solid-state dewetting of Pt films. Similarly, Ag NPs evolved from elongated shape at low temperatures to oval, and eventually to spherical shape as the temperature and annealing time increased in the solid-state dewetting of thin Ag films in air.…”
Section: ■ Experimental Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This shape evolution was also observed in solid-state dewetting of 40 nm Pt films on an adhesion layer of ZnO where faceted Pt islands changed to rounded shape with longer annealing time at 900 °C. 30 Kunwar et al 31 observed the change in the Pt NP shape from irregular to semispherical to hexagonal when the temperature was increased from 700 to 900 °C in their work on using an In sacrificial layer to enhance solid-state dewetting of Pt films. Similarly, Ag NPs evolved from elongated shape at low temperatures to oval, and eventually to spherical shape as the temperature and annealing time increased in the solid-state dewetting of thin Ag films in air.…”
Section: ■ Experimental Methodsmentioning
confidence: 99%
“…30 An enhanced solid-state thermal dewetting of Pt thin films was achieved under vacuum using an indium (In) layer as a sacrificial layer on the sapphire substrates, with a total thickness of Pt and In ranging from 10 to 100 nm. 31 The surface morphology of produced Pt NPs was shown to depend on the In/Pt thickness ratio and the temperature. Recently, Bonvicini et al 32 used the conventional thermal dewetting of 1.4−3.7 nm Pt films on Si (100) substrates in vacuum for the formation of Pt nanostructures.…”
Section: ■ Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Further work to improve the ALD selectivity can be performed by optimizing the ALD reaction condition and by using a more chemically inert silane as the inhibition layer (e.g., polyfluorinated silane). In addition to its implications to the nanoelectronics industry, this work is also of relevance to many applications in photonics, such as enhancing the emission efficiency of UV emitters, 42 fabrication of Pt-based localized surface plasmon resonance structures, 43 and photocatalysis using TiO 2 /Pt heterostructures. 44 ■ EXPERIMENTAL SECTION Materials.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…Over the past decade, many SSG systems have been developed based on different types of photothermal materials, such as metals [ 23 25 ], semiconductors [ 26 28 ], polymers [ 29 31 ], biomass carbon materials [ 32 34 ], MXenes [ 35 ], and graphenes [ 36 38 ]. Among them, plasmonic metal nanomaterials (Au [ 39 41 ], Ag [ 42 44 ], Pd [ 45 , 46 ], Pt [ 47 , 48 ], etc.) have aroused extensive attention due to their localized surface plasmon resonance (LSPR) property.…”
Section: Introductionmentioning
confidence: 99%